Carbon loss from an unprecedented Arctic tundra wildfire - Mack, Michelle C.; Bret-Harte, M. Syndonia; Hollingsworth, Teresa N.; Jandt, Randi R.; Schuur, Edward A. G.; Shaver, Gaius R.; Verbyla, David L. (Nature (London), 2011)
Large carbon release from Alaskan tundra fire In 2007, an area of more than 1,000 square kilometres of Alaskan tundra was destroyed by a single fire, more than doubling the cumulative area burnt in this region since 1950. Michelle Mack and colleagues now show that, in the process, 2.1 teragrams of carbon was released and about one-third of soil organic matter burned away, thereby potentially exposing permafrost soils to thaw. The amount of carbon released from the entire burn was comparable to the annual net carbon sink of the entire Arctic tundra biome during the past 25 years of the twentieth century. As tundra fires are expected to increase as the climate warms, combustion of 'old growth' tundra soil could constitute a positive climate feedback, by transferring surface soil carbon to the atmosphere and accelerating the thaw and decomposition of deeper permafrost carbon. Arctic tundra soils store large amounts of carbon (C) in organic soil layers hundreds to thousands of years old that insulate, and in some cases maintain, permafrost soils 1 , 2 . Fire has been largely absent from most of this biome since the early Holocene epoch 3 , but its frequency and extent are increasing, probably in response to climate warming 4 . The effect of fires on the C balance of tundra landscapes, however, remains largely unknown. The Anaktuvuk River fire in 2007 burned 1,039 square kilometres of Alaska’s Arctic slope, making it the largest fire on record for the tundra biome and doubling the cumulative area burned since 1950 (ref. 5 ). Here we report that tundra ecosystems lost 2,016 ± 435 g C m −2 in the fire, an amount two orders of magnitude larger than annual net C exchange in undisturbed tundra 6 . Sixty per cent of this C loss was from soil organic matter, and radiocarbon dating of residual soil layers revealed that the maximum age of soil C lost was 50 years. Scaled to the entire burned area, the fire released approximately 2.1 teragrams of C to the atmosphere, an amount similar in magnitude to the annual net C sink for the entire Arctic tundra biome averaged over the last quarter of the twentieth century 7 . The magnitude of ecosystem C lost by fire, relative to both ecosystem and biome-scale fluxes, demonstrates that a climate-driven increase in tundra fire disturbance may represent a positive feedback, potentially offsetting Arctic greening 8 and influencing the net C balance of the tundra biome.